Pengaruh Hunger Marketing terhadap Perceived Value untuk Meningkatkan Pembelian Tidak Terencana (Jurnal Ekonomi dan Bisnis Islam, 2023)
This research is used to find out about hunger marketing which includes anchor characteristics, online comments, logistics service quality, promotion incentive information and promotion time limits on perceived value and impulsive buying in live e-commerce. This study used a sample of 165 respondents. the withdrawal method uses probability sampling with the Simple Random technique. This research is aimed at members of Fatayat NU, Kkudus Regency, who have shopped online at e-commerce. Data analysis techniques using Structural Equation Modeling (SEM) 24.0. and the results show that there is no influence on the perceived value, namely the Promotion Time limit.Keywords: Hunger Marketing, Perceived value, and Impulsive buying behavior